2023
DOI: 10.1021/acs.analchem.3c00436
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of MMP-Independent Near-Infrared Fluorescent Probes for Accurately Monitoring Mitochondrial Viscosity

Abstract: Mitochondrial viscosity affects metabolite diffusion and mitochondrial metabolism and is associated with many diseases. However, the accuracy of mitochondria-targeting fluorescent probes in measuring viscosity is unsatisfactory because these probes can diffuse from mitochondria during mitophagy with a decreased mitochondrial membrane potential (MMP). To avoid this problem, by incorporating different alkyl side chains into dihydroxanthene fluorophores (denoted as DHX), we developed six near-infrared (NIR) probe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Previous studies have reported that the ionic carriers, monensin (Mon), nystatin (Nys), and lipopolysaccharides (LPS), disrupt ion homeostasis, leading to mitochondrial dysfunction and viscosity changes. 36–40 In addition, carbonyl cyano-chlorophenyl hydrazone (CCCP) can also cause changes in mitochondrial viscosity. 41 Therefore, to investigate the monitoring of intracellular mitochondrial viscosity changes by YPE , we used different drug stimuli to regulate changes in the mitochondrial microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that the ionic carriers, monensin (Mon), nystatin (Nys), and lipopolysaccharides (LPS), disrupt ion homeostasis, leading to mitochondrial dysfunction and viscosity changes. 36–40 In addition, carbonyl cyano-chlorophenyl hydrazone (CCCP) can also cause changes in mitochondrial viscosity. 41 Therefore, to investigate the monitoring of intracellular mitochondrial viscosity changes by YPE , we used different drug stimuli to regulate changes in the mitochondrial microenvironment.…”
Section: Resultsmentioning
confidence: 99%
“…Due to their excellent biocompatibility and programmability, DNA nanostructures have been widely used in the construction of fluorescent DNA nanosensors and cell imaging. Among them, the near-infrared (NIR) DNA nanosensors can avoid the influence of luminescence in the organism to the greatest extent and can also pass through the skin, fat, and other tissues to a greater extent, so NIR DNA nanosensors has its unique advantages in biological detection. The sensing mechanism of traditional fluorescent DNA nanosensors mostly depends on the change in the distance between the fluorophore and quencher. As shown in Figure a, the change of target concentration leads to the change of DNA structure, which in turn changes the distance between fluorophore and quencher and produces fluorescence signal.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the conjugated structure with long alkyl chains of different lengths may exhibit similar or distinct staining results. Therefore, we synthesized DMPQ-n (n = 8, 10, and 14) to examine the effect of the alkyl chain length of the probes on their localization in fixed cells. The absorption and fluorescence spectra of DMPQ-n in different solvents are displayed in Figures S22–S24, and their optical properties are summarized in Table S2.…”
mentioning
confidence: 99%